Human interface and the management of information. information in applications and services : 20th International Conference, HIMI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: information in applications and services : 20th International Conference, HIMI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available